The Evolution of Climate Change Coverage in the Spanish Press (2000–2024) (Tempo e Argumento, 2026)
Climate change is recognized as a paramount challenge for humanity. In recent years, an acceleration in the rise of temperatures has been recorded in both the atmosphere and the oceans, alongside numerous impacts across all regions of the world. Spain is experiencing its effects, as evidenced by numerous extreme weather events. This study seeks to identify the quantitative coverage of climate change in the Spanish print press from January 1, 2001 to December 31, 2024. It counts articles containing the terms “climate change” or “global warming” in the Spanish newspapers analyzed by MeCCO (Media Climate Change Observatory) at the University of Colorado: El País, El Mundo, La Vanguardia and Expansión. The methodology used is content analysis. The results show that the newspaper publishing the largest number of articles is the progressive daily El País; November is the month with the greatest coverage, coinciding with the Climate Summits; the years with the most references were 2007, 2019, and 2021; the period 2020–2024 constitutes the five-year span of greatest media attention, although a decline is observed toward the end of this period; and there is a considerable parallelism between coverage trends in the Spanish press and the global press. In conclusion, the consolidation of climate change coverage in the Spanish press is considered necessary, in line with its potential impact.
Keywords: climate change; communication; media coverage; Spain; press